2016
DOI: 10.3748/wjg.v22.i44.9674
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver is associated with an increased risk of diabetes and cardiovascular disease - Evidence from three different disease models: NAFLD, HCV and HIV

Abstract: Fatty liver, which frequently coexists with necro-inflammatory and fibrotic changes, may occur in the setting of nonalcoholic fatty liver disease (NAFLD) and chronic infections due to either hepatitis C virus (HCV) or human immunodeficiency virus (HIV). These three pathologic conditions are associated with an increased prevalence and incidence of cardiovascular disease (CVD) and type 2 diabetes (T2D). In this multidisciplinary clinical review, we aim to discuss the ever-expanding wealth of clinical and epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 262 publications
(309 reference statements)
1
76
0
5
Order By: Relevance
“…The incidence of HCV-related insulin resistance is independent of the stage of liver disease. On the other hand, HCV-related insulin resistance and type 2 DM accelerate the development of liver fibrosis, cirrhosis, and hepatocellular carcinoma, while HCV clearance following antiviral treatment is associated with improved insulin resistance and reduced incidence of type 2 DM [9, 29, 30]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of HCV-related insulin resistance is independent of the stage of liver disease. On the other hand, HCV-related insulin resistance and type 2 DM accelerate the development of liver fibrosis, cirrhosis, and hepatocellular carcinoma, while HCV clearance following antiviral treatment is associated with improved insulin resistance and reduced incidence of type 2 DM [9, 29, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Among viral infections, hepatitis C virus (HCV) infection was ascribed a possible role in the onset of type 2 DM because of the ability of HCV to induce insulin resistance, the higher prevalence of type 2 DM in HCV-infected patients compared to noninfected cases, as well as improvement in insulin resistance following antiviral therapy [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…While NAFLD may be associated with progressive liver disease in the forms of non-alcoholic steatohepatitis (NASH), hepatic fibrosis, and, ultimately, cirrhosis, liver failure and hepatocellular carcinoma[71], CVD accounts for most of the excess morbidity and mortality associated with NAFLD[72, 73]. This association with morbidity and mortality is independent of traditional CVD risk factors[74], but is tightly linked to excess adiposity and its consequences.…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%
“…Whilst there are a number of controversies, some evidence may suggest an involvement of HCV in the development of cardiovascular complication, insulin resistance, hepatic steatosis, and T2DM as a common link (26). In the current study, hypertension was observed in 12.1% of the patients.…”
Section: Discussionmentioning
confidence: 58%